The effect of ripening medium (goat skin bag or plastic barrel) on the volatile profile, color parameter and sensory characteristics of Tulum cheese - Tekin, Ali; Guler, Zehra (Univ Zagreb, Fac Agriculture, 2021)
The objective of this study was to determine volatile compounds, color parameters and sensory characteristics in raw sheep milk cheeses ripened up to 270 days using different packaging materials such as goat's skin bag or plastic barrel. Volatile compounds extracted by solid-phase microextraction were separated, identified and quantified using a gas chromatography (GC)-mass spectrometry detector (MS). Butanoic acid, hexanoic acid, octanoic acid, ethanol, ethyl acetate, ethyl butanoate, ethyl hexanoate, 2-butanol, 2-butanone and 2-heptanone were the predominant compounds in the volatile fraction of the cheeses. Among these, ethanol was the most abundant at the first 180 days of cheese ripening but there were 2-butanol and 2-butanone for cheese in plastic barrel (PB) and 2-heptanone for cheese in goat's skin bag (GS) at the 270 days. To best acknowledge, m-cimene, alpha-cubebene, trans-caryophylene, delta-cadinene and 16-oxasalutaridine were identified for the first time in sheep milk and its cheese. Discriminant analysis based on volatile compounds classified the cheeses according to their ripening times and also packaging materials. At the end of the ripening the differentiation between GS and PB cheeses was more evident. The results showed that GS cheese was more preferred by panelists. Cheeses ripened for more 180 days, in particular PB cheese, were much less acceptable to panelists. Therefore, in terms of optimum overall acceptability, 90 and 180 days ripening periods could be advised for the producers for PB and GS cheeses, respectively.
Keywords: sheep milk; tulum cheese; ripening; volatile; color; sensory